(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article presents the development of a new automated design to improve the efficiency of flat solar collectors (FSC) with the organization of thermal insulation on the absorber of thermal FSC at night. The technology of an automated design, a schematic diagram of the automatic functioning of the system and the results of experimental studies are presented.